FACTORS AFFECTING THE ACTIVITY CENTER COMMUNITY (CLC) CASE STUDY: CLC GASIB BEAUTIFUL IN DISTRICT DISTRICT KOTO GASIB SIAK - Siti Patimah; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The growing need for non-formal education services in the midst of society, the various components of society feel compelled to participate in setting up the CLC. CLC held aims to provide non-formal education as an enhancer, substitutes and complements formal education for citizens who need the knowledge, skills, life skills, develop self strive for independence, and or continuing education a higher level of community empowerment. Therefore, the principle of CLC is of, by, and for the public formulation of the problem in this study what factors are affecting the community learning center (CLC) Gasib Beautiful in District Koto Gasib Siak 2016 and barriers?The purpose of this study was to determine the Factors that affect the community learning center (CLC) Gasib Beautiful in District Koto Gasib Siak 2014 and resistance. The technique used to collect data in this study were (1) Interviews (2) Documentation.The conclusion of this study is Based on the research that has been done Concerning Factors That Affect Community Learning Center (CLC) Case Study: CLC Gasib Beautiful In District Koto Gasib Siak In 2014 researchers were able to conclude that, coaching is done by the District Head, Department of Education and Culture, PKBM against Community Learning Center is not maximized. Limited funding constraints ie, coordination of work, as well as the lack of public knowledge of the Community Learning Center (CLC) Gasib Beautiful Koto Gasib subdistrict.Keywords: Role, Coaching, Community Development